The Effect Of Profitability, Leverage, And Firm Size On Sustainability Report Disclosure - Sherly Yohana; Rousilita Suhendah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2023)
This study aims to determine the effect of profitability, leverage, and firm size on sustainability report disclosure in healthcare, energy, and financial sector companies listed on the Indonesia Stock Exchange in the 2019 to 2021 period. Samples were selected using non-probability sampling and purposive sampling techniques, and the data obtained consisted of 12 companies. Data were processed using the EViews (Econometric Views) version 12 program. The results of this study indicate that profitability and leverage have a positive and significant effect on sustainability report disclosure, while firm size does not affect sustainability report disclosure. This research implies that companies with high levels of funds tend to make broader sustainability report disclosures, so to obtain a high level of sustainability report disclosure requires a large amount of funds, which can also be obtained from the company's operating profit or by borrowing funds (debt) to creditors.